Udział tlenku azotu w procesach fizjologicznych i patologicznych zachodzących w oku - Komaszyło, Katarzyna; Zalewska, Renata; Mariak, Zofia; Wiśniewska, Róża (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Nitric oxide (NO) is a gas with diverse biological activities produced from arginine by nitric oxide synthetase (NOS). The loss of retinal ganglion cells is a hallmark of many ophthalmic diseases including glaucoma, retinal ischemia due to central artery occlusion and anterior ischemic optic neuropathy. It may well be significant in optic neuritis, optic nerve, trauma and AIDS. NO appears to be involved in the regulation of intraocular pressure, in the modulation of ocular blood flow and in apoptosis. This article gives a short and simplified overview of the biochemistry of NO and its role in physiology and pathogenesis of ocular diseases.